Reporting quality of clinical trial protocols: a repeated cross-sectional study about the Adherence to SPIrit Recommendations in Switzerland, CAnada and GErmany (ASPIRE-SCAGE) - Gryaznov, D; von Niederhäusern, B; Speich, B; Kasenda, B; Ojeda-Ruiz, E; Blümle, A; Schandelmaier, S; Mertz, D; Odutayo, A; Tomonaga, Y; Amstutz, A; Pauli-Magnus, C; et al. (BMJ Publishing Group, 2022)
Objectives Comprehensive protocols are key for the planning and conduct of randomised clinical trials (RCTs). Evidence of low reporting quality of RCT protocols led to the publication of the Standard Protocol Items: Recommendations for Interventional Trials (SPIRIT) checklist in 2013. We aimed to examine the quality of reporting of RCT protocols from three countries before and after the publication of the SPIRIT checklist.